Total Thrombus‐Formation Analysis System (T‐TAS) Can Predict Periprocedural Bleeding Events in Patients Undergoing Catheter Ablation for Atrial Fibrillation. Issue 1 (25th January 2016) - Ito, Miwa; Kaikita, Koichi; Sueta, Daisuke; Ishii, Masanobu; Oimatsu, Yu; Arima, Yuichiro; Iwashita, Satomi; Takahashi, Aya; Hoshiyama, Tadashi; Kanazawa, Hisanori; Sakamoto, Kenji; Yamamoto, Eiichiro; et al.
Abstract : Background: Non–vitamin K antagonist oral anticoagulants are used to prevent thromboembolism in patients with atrial fibrillation. The T‐TAS "Total Thrombus‐formation Analysis System" (Fujimori Kogyo Co Ltd) was developed for quantitative analysis of thrombus formation using microchips with thrombogenic surfaces (collagen, platelet chip [PL] ; collagen plus tissue factor, atheroma chip [AR]). We evaluated the utility of T‐TAS in predicting periprocedural bleeding in atrial fibrillation patients undergoing catheter ablation (CA). Methods and Results: After exclusion of 20 from 148 consecutive patients undergoing CA, the remaining 128 patients were divided into 2 treatment groups: the warfarin group (n=30) and the non–vitamin K antagonist oral anticoagulants group (n=98). Blood samples obtained on the day of CA (anticoagulant‐free point) and at 3 and 30 days after CA were used in T‐TAS to compute the thrombus formation area under the curve (AUC; AUC for the first 10 minutes for PL tested at flow rate of 24 μL/min [PL24 ‐AUC10 ]; AUC for the first 30 minutes for AR tested at flow rate of 10 μL/min [AR10 ‐AUC30 ]). AR10 ‐AUC30 and PL24 ‐AUC10 levels were similar in the 2 groups on the day of CA. Levels of AR10 ‐AUC30, but not PL24 ‐AUC10, were significantly lower in the 2 groups at days 3 and 30 after CA. Multiple logistic regression analyses identified the AR10 ‐AUC30 level on the day of CA as a significant predictor of periprocedural bleeding events (odds ratio 5.7; 95% CI 1.54–21.1; P =0.009). Receiver operating characteristic analysis showed that the AR10 ‐AUC30 level on the day of CA significantly predicted periprocedural bleeding events (AUC 0.859, 95% CI 0.766–0.951; P <0.001). The cutoff AR10 ‐AUC30 level was 1648 for identification of periprocedural bleeding events. Conclusions: These results suggested that the AR10 ‐AUC30 level determined by T‐TAS is a potentially useful marker for prediction of bleeding events in atrial fibrillation patients undergoing CA.